2019
DOI: 10.3390/ijerph16081398
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life and Its Determinants among Criminal Police Officers

Abstract: Criminal police officers are viewed as having a very tiring and stressful job, one that is closely correlated with work disability and other factors that might impair quality of life. Few studies have addressed the issue of health-related quality of life (HRQoL) in this population. Thus, this study aimed to assess the HRQoL of criminal police officers compared with the general adult population and identify determinants associated with HRQoL. Based on a cross-sectional study of 281 criminal police officers in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 52 publications
3
17
0
5
Order By: Relevance
“…Police work is considered stressful and dangerous because of exposure to confrontation, violence, and traumatic incidents, including the possibility of being injured or killed [30,31]. In this sense, Cannizo and Liu [32] frame police activity among the service professions that demand both emotional stability and the skill to make quick decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Police work is considered stressful and dangerous because of exposure to confrontation, violence, and traumatic incidents, including the possibility of being injured or killed [30,31]. In this sense, Cannizo and Liu [32] frame police activity among the service professions that demand both emotional stability and the skill to make quick decisions.…”
Section: Introductionmentioning
confidence: 99%
“…In view of this, it was observed in workers with SAH the existence of risk factors for cardiovascular problems and for cardiac alterations related to daily life habits, factors that have an impact on the quality of life manifested by civil police officers. Thus, corroborating with authors, interventions in the workplace of police officers are necessary, including recruitment of employees, better work organization and promotion of resources in order to support the well-being of police officers (16) , as well as actions focused on the reformulation of organizational and public policies aimed at preventing occupational risks and diseases (22) .…”
Section: Discussionmentioning
confidence: 60%
“…A study carried out in South China, with the objective of evaluating the health-related quality of life of police officers, found lower quality of life in this group when compared to the adult population in general, and that anxiety/depression was the most frequently reported problem. Age, alcohol consumption, physical activity, occupational damage and anxiety/depression symptoms significantly influenced the decrease in quality of life (16) .…”
Section: Discussionmentioning
confidence: 99%
“…Most of the patients in both groups showed a stable EQ-5D score so that there was no difference in HRQOL between the two groups. These conditions may be influenced by several factors such as work, education, marital status, and other comorbid diseases (21,22) . Based on previous studies by Yang et al, it was found that the Quality of Life (QoL) score using the EQ5D score and the WHO QoL -Brief questionnaires in patients who received Afatinib therapy was lower than in the Gefitinib group but not significantly different in the Gefitinib group compared with the Erlotinib group.…”
Section: Discussionmentioning
confidence: 99%